Assessment of Thyroid Dysfunction among Patients with Type II Diabetes Mellitus (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Endocrine disorders are the chronic disorders leading to the significant morbidity. The aim of the study was to find the occurrence of the thyroid dysfunction among the patients with type 2 diabetes mellitus and to analyse the prescribing patterns.Methods: This is a retrospective study conducted among 180 in-patients of age above 30 years, diagnosed with type II diabetes mellitus along with thyroid dysfunction, admitted in general medicine unit. Patients with type I diabetes mellitus and pregnant women with thyroid disorders were excluded from the study. All the relevant data were collected from patient case notes. The assessment was carried out by using descriptive statistics.Results: Out of a total 180 patients, females (67.8%) outnumbered the male (32.2%) patients. Higher frequency of disease was observed in an age group of 60-69 years (38.33%). Many patients were reported to have type II diabetes mellitus for a period of 1-5 years before the diagnosis of thyroid dysfunction. Oral hypoglycaemic agents were commonly used to manage type II diabetes mellitus, in which metformin was the most frequently prescribed drug. Hypothyroidism was treated with levothyroxine and carbimazole was frequently used to treat hyperthyroidism.Conclusion: The occurrence of diabetes with thyroid dysfunction was higher in females. Hypothyroidism was the most common thyroid disorder and was treated by levothyroxine. Oral hypoglycaemic agents were commonly used to treat the hyperglycaemias. Similarly, carbimazole was most frequently used to treat the hyperthyroidism.